Pregnancy outcomes following gestational exposure to papaverine: An observational comparative study. Issue 10 (20th March 2021) - Gueta, Itai; Braun, Adi; Gilan, Adi; Berlin, Maya; Kohn, Elkana; Barchel, Dana; Markovits, Noa; Berkovitch, Matitiahu; Loebstein, Ronen
Abstract : Aims: Papaverine is indicated for abdominal pain of various aetiologies. However, data on maternal and foetal safety following gestational exposure are lacking. The aim was to examine whether first trimester exposure to papaverine is associated with increased risk for major malformation and whether gestational exposure at any stage is associated with increased risk for preterm delivery, lower birthweight, small for gestational age, caesarean section (CS), lower Apgar score and perinatal death. Methods: A retrospective comparative study consisted of pregnant women treated with papaverine between February 2010 and October 2019 at a large tertiary center. The control group comprised of livebirth deliveries randomly selected from the institutional obstetric database. Results: The study group consisted of 498 pregnancies, which resulted in 537/544 (98.7%) live births, of whom 46/537 (8.6%) were exposed during the first trimester. The control group consisted of 498 pregnancies and 514 live births. Rate of major malformations did not differ between study group (2/46, 4.3%) and control (25/315, 4.9%, P =  .67). Papaverine exposure was associated with higher rate of preterm delivery (22.3 vs . 10.3%, P <  .001), CS (35.9 vs . 24.1%, P <  .001) and lower birth weight (3207 vs . 3246 g, P =  .02). Adjustment for treatment indication demonstrated that these remained significant only when given for obstetrical/surgical aetiologies. Comparable rates were observed for the remaining outcomes. Conclusions: Short‐term gestational exposure to papaverine adjusted for indication was not associated with preterm deliveries, CS, lower birthweight, small for gestational age or perinatal death. Rate of major malformations among 46 first trimester exposures was comparable to controls.